Investigation of the Comorbidity of Bronchial Asthma and Allergic Rhinitis in Children - Madridovich, Mirzakhanov Said; Magomedovich, Abdulkhalikov Magomedsaid; Raidinovna, Nazila Abdurakhmanova; Abdullatipovna, Amangulova Diana; Shakhmuradovna, Zalova Bella; Abubakarovna, Salmakhanova Khadidja; Aligadzhievich, Aliev Magomedrasul; Abubakarovich, Salmakhanov Abusufyan (International Journal of Membrane Science and Technology, 2024)
Today there is an increasing tendency for all allergic diseases, including a high prevalence of bronchial asthma (BA), as well as an increasing number of patients with co-morbidities. Allergic rhinitis leads in frequency of occurrence with bronchial asthma. In the last decade, the term comorbidity has often been used to define the interrelation as well as the mutual influence of 2 or more syndromes, diseases in one patient. The aim of the research was to study the comorbidity of bronchial asthma and allergic rhinitis in children in the Department of Pulmonology. The retrospective study included an analysis of 51 case histories of children diagnosed with atopic bronchial asthma. Of the 51 patients, 28 children (54.9±7%) were diagnosed with allergic rhinitis after examination by an ENT specialist.